Nitrite is a more efficient inhibitor of microbial sulfate reduction in oil reservoirs compared to nitrate and perchlorate: A laboratory and field-scale simulation study. (February 2021) - Veshareh, Moein J.; Kjeldsen, Kasper U.; Findlay, Alyssa J.; Nick, Hamidreza M.; Røy, Hans; Marietou, Angeliki
Abstract: Microbial sulfate reduction is the most significant source of hydrogen sulfide (souring) as oil reservoirs are flooded with seawater (with mM concentrations of sulfate) for secondary oil recovery. Nitrate (nitrite) injections into the reservoirs are routinely used to constrain souring. Perchlorate was proposed as an alternative souring mitigation agent, however its effectiveness remains to be determined on a field scale. We used a combination of laboratory-based experiments and field scale numerical models to compare the efficacy of nitrate, nitrite, and perchlorate in inhibiting sulfide production in offshore oil reservoirs. Our results suggest that on a field scale perchlorate inhibits sulfide accumulation by inhibiting sulfate reduction and promoting sulfide oxidation. Elemental sulfur production was observed during nitrate reduction by Archaeglobus fulgidus confirming previous suggestions that the process is coupled to the oxidation of sulfide. Finally, nitrite was the most efficient inhibitor of sulfide accumulation, further confirmed by our field scale simulations. Our field scale simulations predict that injection of 1 mM of nitrite can reduce souring by 92%, while perchlorate (1 mM) or nitrate (1 mM) have the potential to reduce sulfide accumulation by 57% and 80% respectively. Graphical abstract: Image 1 Highlights: Desulfobacterium autotrophicum can reduce sulfate to sulfide in the presence of 20 mM of perchlorate. Archaeglobus fulgidus couples nitrate reduction to the chemical oxidation of sulfide to elemental sulfur. Nitrite is the most efficient souring mitigation approach compared to nitrate and perchlorate. Nitrite injection can reduce souring by up to 92%.